Codling moth management by low doses of sugars on the Royal Gala variety - Abdelkader Tiffrent; Nadia Lombarkia (Acta Agriculturae Slovenica)
Codling mo th (CM) is a key pest in apple orchards in Algeria. Its control is difficult because of its ability to develop resistance to pesticides. Besides, concern about the safety of these pesticides for human health and the environment has led to regulatory actions that have reduced the availability of these products to growers. Thus, the use of eco-friendly alternative methods is encouraged. In this context, foliar spraying using fructose (100 ppm) and glucose (100 ppm) against CM larval stages on the Royal Gala variety, compared to the control and insecticide (Deltamethrin), was assessed in an orchard located in Beni Fedhala province (Batna-Algeria). The obtained results confirmed that the spraying of glucose and fructose increased the percentage of healthy fruits at harvest, the percentages of healthy fallen fruits and the total healthy fruits. Further, the number of diapausing larvae in corrugated cardboard banding was reduced. In addition, our study  shows that the number of chrysalis was significantly lower and different from the number of male and female larvae, which are identical.